Perbandingan Keterampilan Motorik Kasar Anak Kelompok B pada Kegiatan Senam Berirama dan yang Tidak Berirama - Ani Marlia; Titin Faridatun Nisa'; Yulias Wulani Fajar (PG-PAUD Trunojoyo, 2018)
The aim of this study is to compare applying music through gross motor skill towards kid’s Class B Kindergarten on gymnastic. This study using comparative quantitative approach with 30 kids; 15 boys and 15 girls as the research subject. It takes from the population of Ulil Albab Kindergarten students using purposive sampling considers criteria towards their development. Observation and documentation technique are applied as data interpretation. Therefore, the instrument of study utilizes observation sheet from the kid’s gymnastics at school. The data analysis uses statistic non-parametric. Wilcoxon test is used in this study as the hypothesis result. Ensue from the computation SPSS 19.0 is as two directions significant 0, 00. According to this significant 0,05 thus Ho is confirmed. This shows there is no difference of gross motor towards Class B kids in using music on gymnastics.